Case Report: Two clinical cases of Wilms tumor comorbid to gingival fibromatosis in young children with constitutionally mutated REST - Salomatina, Anastasiya S.; Yasko, Liudmila A.; Kurnikova, Maria A.; Mareeva, Yulia M.; Abasov, Ruslan K.; Gegeliya, Nina V.; Mitrofanova, Anna M.; Usman, Natalia Y.; Novichkova, Galina A.; Druy, Alexander E. (Frontiers in Oncology, 2023)
Introduction Nephroblastoma (Wilms tumor (WT)) is an embryonal tumor accounting for >90% of pediatric renal cancers. About 10% of WTs harbor pathogenic germline mutations. The REST gene, classified as a putative tumor suppressor, is affected in 2% of WTs. High-throughput molecular methods facilitate advanced diagnostics of cancer. In addition to this, germline mutations in REST are also associated with familial gingival fibromatosis (GFM). Reciprocally, none of the articles on RESTmut WT mentions GFM as a comorbid condition. This report provides unique evidence on the WT-GFM comorbidity in RESTmut carriers. Case presentation Patient 1 (a 5-year-old boy with unilateral WT) is a proband, who has two healthy siblings. Patient 2 (a 4-year-old girl with bilateral WT) is a proband from in vitro fertilization (IVF) triplets, with a sister and brother without WT. We analyzed probands’ DNA extracted from peripheral blood leucocytes with a custom-targeted next-generation sequencing (NGS)-198 gene panel. The detected variants were checked in family members by Sanger sequencing. Patient 1 had a pathogenic germline mutation in REST: c.1035_1036insTA, p.(E346*), as did his mother and both brothers. There were two other WT cases in this family (proband’s maternal uncles). Patient 2 had a pathogenic germline variant in REST: c.2668_2671del, p.(E891Pfs*6), as well as her sister. The mutation was probably inherited from their deceased father, as he had gingival fibromatosis. Family members with REST mutations from both families had gingival fibromatosis. A somatic REST c.663C>A p.C221* mutation was identified in one patient with WT. At the moment both patients with WT are under dynamic observation without signs of the disease. Conclusion Here, we describe two clinical cases of WT in nonrelated young children with germline-inactivating REST variants identified by next-generation sequencing. Both patients present with familial gingival fibromatosis, regarded as clinically useful comorbidity indicative of the tumor predisposition syndrome. The two cases illustrate Wilms tumor-gingival fibromatosis comorbidity in carriers of germline-inactivated REST alleles previously identified as a predisposition factor for both conditions.